CAL and FE: a Welsh perspective - Antje Cockrill; Cliona O'Neill; Eberhard Bischoff; David Finch (Association for Learning Technology, 2000)
The increasing usage in recent years of trendy, but often ill-defined, terms such as 'lifelong learning' (see Edwards, Raggatt, Harrison, McCollum and Calder, 1998), 'the learning society' (for example, National Grid for Learning, http://www.dfee.gov.uk/grid/challenge/ govermhtm), or 'learning country' (for example, Welsh Office, 1998; ETAG, 1999) indicates the importance that both the public and private sectors attach to the establishment of a learning culture. This has included the recognition that, in order to achieve such a culture, access to learning must be made easier and existing barriers removed. Edwards and his coauthors (1998) maintain that most experts see lifelong learning as a rallying cry, rather than a specific policy. This statement holds true for many similar slogans, but what they have in common is 'the power to unite various stakeholders around the need for change, because it has emerged as a response to today's challenges' (Edwards et al, 1998).